It Takes a Village: Listening to Parents - Stephen Bolaji; Sulay Jalloh; Marilyn Kell (MDPI AG, 2020)
The study was premised on the concern of the migrant African parents about their children’s lack of aspiration for higher education after completing their secondary education in the Northern Territory (NT), Australia. There appears to be little understanding of, or confusion around, the different pathways available to higher education in Australia. The reports and anecdotes around African youths in the NT demonstrating antisocial behaviors, including, but not limited to drug offences, teen pregnancies and suicides prompted this research. These troubling behaviors have culminated in the death of two young boys in the African community in Darwin 2016 and another girl in 2019 in Kathrine. The study comprises of African parents who migrated to NT in Australia from different demographics in Africa. This study used a questionnaire and semi-structured interviews to investigate African parents’ perception of their child’s post-secondary school aspiration. The outcome of this investigation revealed a lack of understanding of the NT Australian school systems and reporting strand on their children performance and the different pathways through which their children can access higher education in Australia. This study provided four recommendations to help African parents understand the NT Australian government policies and programs on education.